2020
DOI: 10.7717/peerj.8988
|View full text |Cite
|
Sign up to set email alerts
|

Understanding PM2.5 concentration and removal efficiency variation in urban forest park—Observation at human breathing height

Abstract: To increase our knowledge of PM2.5 concentrations near the surface in a forest park in Beijing, an observational study measured the concentration and composition of PM2.5 in Beijing Olympic Forest Park from 2014 to 2015. This study analyzed the meteorological factors and removal efficiency at 1.5 m above the ground (human breathing height) over the day in the forest. The results showed that the average concentrations of PM2.5 near the surface peaked at 07:00–09:30 and reached their lowest at 12:00–15:00. Besid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
3
4
0
Order By: Relevance
“…As a result, it was concluded that relative humidity and temperature were the most important meteorological variables influencing PM 2.5 concentration. Previous research ( Deng et al., 2019 ; Yan et al., 2020 ; Liu et al., 2015 ) has found a strong significant association between PM 2.5 and relative humidity and temperature, which is in line with our findings. Other research, on the other hand, had come up with different findings.…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…As a result, it was concluded that relative humidity and temperature were the most important meteorological variables influencing PM 2.5 concentration. Previous research ( Deng et al., 2019 ; Yan et al., 2020 ; Liu et al., 2015 ) has found a strong significant association between PM 2.5 and relative humidity and temperature, which is in line with our findings. Other research, on the other hand, had come up with different findings.…”
Section: Resultssupporting
confidence: 94%
“…The decrease of boundary layer height and wind speed in the afternoon hours along with the increased source activities during the afternoon rush hour, consequently, resulted in high PM 2.5 concentration during evening hours. Similar trend was observed by the previous studies ( Yan et al., 2020 ; Wang et al., 2014 ; Zhao et al., 2009 ) where they studied the diurnal variation of PM 2.5 concentration in the ambient air in the urban areas.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations